Republic of Mozambique : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper on the Republic of Mozambique highlights that in the period 1987-97, the economy of Mozambique made impressive gains. Real GDP and exports grew on average by 6.8 percent and 15.6 percent, respectively, and the ratio of investment to GDP rose from 36.1 percent in 1987 to 45.2 percent in 1997. In the two years ended December 1996, the 12-month inflation rate fell dramatically from 70.1 percent to 16.6 percent.